The Impact of Social Media on Voters' Perceptions in the 2024 Election - Najwa Shafira Mulia; Ervina Auralia; Moch Maulana Hasanudin; Dedi Mulyadi; Reda Musyarir (PT Syamilah Literasi Islami, 2024)
This research aims to analyze the impact of social media on voter perceptions in the 2024 Election, studied according to Law Number 7 of 2017 concerning General Elections in conjunction with Law Number 11 of 2008 concerning Information and Electronic Transactions. This research uses qualitative methods with a normative juridical approach. Primary data was obtained through interviews with constitutional law experts, political communication experts, and election monitoring activists. Secondary data was obtained from literature studies, such as books, scientific journals, and statutory regulations. The research results show that social media has both positive and negative impacts on voter perceptions. As a positive impact, social media can increase political participation and access to voter information. The negative impact is that social media can be used to spread hoaxes, hate speech and political propaganda which can manipulate voter perceptions. Based on the research results, it was concluded that stricter regulation and supervision of the use of social media in elections is necessary. This needs to be done to ensure that social media is used responsibly and does not manipulate voter perceptions.